Simulation and optimization of CNC cylindrical grinder Performance based on equivalent analysis of joints spring-damping characteristics - Qi Mingzheng; Wang Han; Sun Xizhi; Li Tianjian; Guo Yang; Wu Tao (International Journal of Metrology and Quality Engineering)
This paper focuses on the MKE1620A CNC cylindrical grinder, using an equivalent analysis of the joint spring-damping characteristics to investigate the overall performance of the grinder and propose directions for design optimization. A total of 168 spring-damper elements were established to model the fixed, movable, and bearing joints. These elements were classified and calculated to determine their parameters, which were then incorporated into a finite element analysis model to examine the impact of joint stiffness on the static and dynamic performance of the machine tool, with results showing less than a 10% error compared to actual measured data. Additionally, the paper investigates how the quality of six common structural materials influences the first-order natural frequency of components and explores the relationship between variations in joint stiffness and changes in the machine tool’s natural frequency. The findings provide theoretical and data-driven insights for the design and optimization of CNC cylindrical grinding machines, serving as a valuable reference for enhancing machine tool performance and machining quality.